A Review on Cracked Tooth Syndrome - Loganathan Saatwika1 , Venkatachalam Prakash2 , Dhakshinamoorthy Malarvizhi2 , Arunajetasan Subbiya3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cracked tooth syndrome(CTS) remains a big challenge to dentist because of its variable, bizarre clinicalpresentation, unpredictable symptoms and diagnostic dilemma. Based on the severity of the symptoms anddepth of tooth structure involved, the treatment planning and management of CTS varies from one case toanother or from one tooth to another in the same individual. The prognosis of such tooth continues to bequestionable and needs continuous analysis. This article aims to resolve some of the confusion surrroundingtooth cracks diagnosis and different treatment options.